“Innovative Anatomy assessment methods in COVID-19 Pandemic: statistical observations and students viewpoints” (Bangladesh Journal of Medical Science, 2020)
Background: Currently anatomy training and assessment is seriously disrupted in COVID-19 Pandemic lockdown. New challenges of anatomy curriculum and assessment method development are being attempted based upon resources, expertise and technical skills of educators. This study aims at creating a standard operation procedure (SOP) for conducting gross anatomy assessment, finding statistical relevance and discusses viewpoints of students reflected in feedback.Materials and methods: a retrospective cross sectional study was conducted on 250 first year students at GSVM Medical College Kanpur India. Students were briefed about SOP and were given choice to opt for either of three interview modalities of assessment tool [Viz. Telephonic Interview (GROUP T), Whatsapp© video call (GROUP W) and Zoom© meetings (GROUP Z)] and submit subjective feedbacks to assessor regarding new assessment format. The marks obtained as response distribution were subjected to descriptive statistics. One way ANOVA was applied to test any difference in means at (P